Influence of Inflammatory Cytokines IL-1β and IFNγ on Sarcoplasmic Aggregation of p62 and TDP-43 in Myotubes - Bryony McCord; Richard M. Day (Mediators of Inflammation)
Skeletal muscle of patients with sporadic inclusion body myositis (sIBM) presents with inflammation, including upregulation of inflammatory cytokines such as interferon γ (IFNγ). Non-inflammatory features are also observed, like the sarcoplasmic accumulation of proteins including TDP-43 and p62. This study aimed to investigate the effect of IFNγ and interleukin 1-β (IL-1β) on TDP-43 and p62 aggregation in vitro. Primary human myotubes were treated with IL-1β (20 ng/mL) and IFNγ (750 ng/mL) separately or combined for 48 hr. Sarcoplasmic TDP-43 aggregates and p62 puncta were assessed using image analysis for size, frequency, and colocalization with each other. Total protein expression of TDP-43, p62 and LC3 was assessed using western blotting. The subcellular localization of TDP-43 was also analyzed using image analysis. Combined IL-1β and IFNγ treatment increased puncta size of p62 compared to control (0.49 ± 0.13 µm2 versus 0.28 ± 0.06 µm2), without affecting puncta frequency or p62 expression but with an increased LC3II/LC3I ratio, suggesting autophagic alterations. IL-1β or IFNγ did not alter p62 puncta size or frequency, suggesting a combined insult of multiple inflammatory mediators is necessary to cause p62 alterations. IL-1β increased p62 protein expression in an autophagy-independent manner. None of the cytokine treatments affected TDP-43 protein expression, size, or frequency of TDP-43 aggregates or localization, suggesting IL-1β and IFNγ may influence TDP-43 processing in human skeletal muscle cells. TDP-43 was localized to the sarcoplasm under control conditions, suggesting this may not be a pathological feature. Overall, sIBM-like TDP-43/p62 features were not triggered by IL-1β and/or IFNγ.